Effect of garlic powder tablet on carotid intima-media thickness in patients with coronary artery disease: A preliminary randomized controlled trial. Issue 2 (April 2013) - Mahdavi-Roshan, Marjan; Zahedmehr, Ali; Mohammad-Zadeh, Ali; Sanati, Hamid-Reza; Shakerian, Farshad; Firouzi, Ata; Kiani, Reza; Nasrollahzadeh, Javad
Background/objectives: This study was designed to investigate whether garlic powder tablets in adjunct to conventional medical treatment could have an effect on carotid intima-media thickness (CIMT) and plasma lipoproteins and lipids in patients with coronary artery disease (CAD). Subjects/methods: A randomized, placebo-controlled, clinical trial was conducted on 56 patients with CAD between the ages of 25 and 75 years. The patients were randomly divided into two groups: garlic group ( n = 27), receiving garlic powder tablet (1200 µg allicin/tab) twice daily and the placebo group ( n = 29), receiving placebo for 3 months. The rate of atherosclerosis progression was measured by B-mode ultrasonography as the increase in CIMT. Results: After 3 months of taking garlic tablets, CIMT values had minor variations (0.009 ± 0.007 mm reduction from baseline), while in the placebo group, an increase in CIMT values was observed (0.04 ± 0.01 mm increase from baseline). After 3 months of treatment, mean CIMT difference from baseline was significantly differ between the two groups ( p < 0.001). Plasma lipids and lipoproteins (total cholesterol, triglycerides, low-density lipoprotein cholesterol, high-density lipoprotein cholesterol, Apolipoprotein A1 and Apolipoprotein B) did not differ between the two groups. Conclusions: The results suggest that dry garlic powder tablet is superior to placebo in prevention of CIMT progression in patients with CAD and may be considered as an adjunct treatment for atherosclerosis.